Valued personality traits in livestock herding Kelpies—Development and application of a livestock herding dog assessment form - Bethany J. Wilson; Elizabeth R. Arnott; Jonathan B. Early; Claire M. Wade; Paul D. McGreevy (PLoS ONE, 2022)
Livestock herding dogs contribute greatly to the rural economy of Australia. However, their selection currently lacks a cohesive or methodical approach. For example, there is no accessible tool for assessing Australian livestock herding dogs’ suitability for work. The purpose of the current study was to devise a herding dog assessment form, the Herding Dog Assessment Form–Personality (HDAF-P), to facilitate collection of data on relevant behavioural phenotypes of large numbers of working Kelpies and to apply the HDAF-P to identify personality traits needed for herding dog performance. The focus was on creating a succinct form that was salient and accessible to livestock herding dog owners. Wherever practical, terms and methods from published personality questionnaires were integrated. Seventeen terms were included as behavioural descriptors in the HDAF-P which was then used by 95 owners to assess a sample of 228 of their working Kelpies. Owners were also asked to rate the overall ability of their dog(s). Of these dogs, 210 (all twelve months or older) were fully described and their data were used in the analysis. Thus, the study was designed to reveal which personality traits are most critical to the overall ability of the herding dogs and to undertake an exploratory analysis of the patterns of dog behaviour revealed by the HDAF-P in non-juvenile dogs. The traits that showed the strongest correlations (using Kendall’s Tau correlation analysis) with overall ability were initiative (T = 0.41, p < 0.001), persistence (T = 0.36, p < 0.001), intelligence (T = 0.32, p < 0.001), confidence (T = 0.36, p < 0.001) and nervousness (T = -0.30, p < 0.001). An exploratory principal component analysis of trait scores revealed that 64.5% of the variance could be explained by four components that share several similarities with those reported by previous dog personality studies. These findings confirm that the HDAF-P has potential for the practical assessment of livestock herding dog personality and can elucidate traits that should be considered for prioritisation in training and breeding to optimise herding dog ability.